Myosin 1f and Proline-rich 13 are transcriptionally upregulated yet functionally redundant in CD4+ T cells during blood-stage Plasmodium infection - Takahiro Asatsuma; Marcela L. Moreira; Hyun J. Lee; Brooke J. Wanrooy; Oliver P. Skinner; Shihan Li; Ivana Rea; Taidhgin Harkin; Saba Asad; Cameron G. Williams; Lynette Beattie; Ashraful Haque (PLoS ONE, 2025)
Plasmodium-specific CD4+ T cells differentiate into effector and memory subsets during experimental malaria, via mechanisms that remain incompletely characterised. By mining scRNA-seq data of CD4+ T cells during Plasmodium chabaudi chabaudi AS infection in mice, we identified two genes previously uncharacterised in T helper cells, long-tailed unconventional myosin 1f (Myo1f) and proline-rich13/taxanes-resistance 1 (Prr13/Txr1), which were upregulated during effector and memory differentiation. Myo1f is reported to regulate motility and granule exocytosis in myeloid and γδ T cells. Prr13/Txr1 is reported to transcriptionally regulate sensitivity to anti-cancer drugs. To test for cell-intrinsic gene function, we generated Plasmodium-specific TCR transgenic, PbTII cells harbouring CD4-promoter driven Cre recombinase and target genes with loxP-flanked essential exons. We validated our approach for the transcription factor Maf, formally demonstrating here that cMaf is essential for T follicular helper (Tfh) cell differentiation in experimental malaria. Next, having generated conditional knockout lines for Myo1f and Prr13, we observed that deficiency in Myo1f or Prr13 had no impact on either clonal expansion, Th1/Tfh differentiation or transit to memory. Additionally, despite continued expression during re-infection, Myo1f was unnecessary for Th1 recall in vivo. Thus, while cMaf is critical for Tfh differentiation in experimental malaria, Myo1f and Prr13, although transcriptionally upregulated, are unnecessary for effector or memory CD4+ T cell responses.